Influence of Service Quality Customer Loyalty And Trust In. Pos Indonesia (Persero) Lubukpakam - Sri Wahyu Ramadhani (Junal Ilmu Manajemen, 2018)
This study aims to Determine the Effect of Service Quality and Trust on Consumer Loyalty. This research is a research that uses quantitative research. With multiple linear regression of the data analysis techniques. The population in this study are all consumers who ship goods at PT. Lubuk Pos Indonesia (Persero) Pakam. The sample in this study were 100 people who used PT. Pos Indonesia (Persero) Lubukpakam. The number of samples is calculated using the Lemeshow formula. The results of this study indicate that the independent variables items, namely service quality (X1) and trust (X2), have a positive and significant effect on consumer loyalty of PT. Pos Indonesia (Persero) Lubukpakam. The results of this study indicate Also the dominant variable that influences the consumer loyalty of PT. Pos Indonesia (Persero) Lubukpakam is service quality (X1).